2017
DOI: 10.1176/appi.ajp.2017.16101180
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability for Alcohol Use Disorder and Rate of Alcohol Consumption

Abstract: Objective Although several risk factors have been identified for alcohol use disorder, many individuals with these factors do not go on to develop the disorder. Identifying early phenotypic differences between vulnerable individuals and healthy controls could help identify those at higher risk. Binge drinking, defined as reaching a blood alcohol level of 80 mg%, carries a risk of negative legal and health outcomes and may be an early marker of vulnerability. Using a carefully controlled experimental paradigm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 38 publications
8
105
0
1
Order By: Relevance
“…One hundred and sixty social drinkers and 48 heavy drinkers were recruited to participate in an alcohol self‐administration paradigm as part of three studies. The purpose of the first study was to examine determinants of intravenous alcohol self‐administration in social drinkers. The second and third studies sought to examine the effects of medications on intravenous alcohol self‐administration in heavy drinkers .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred and sixty social drinkers and 48 heavy drinkers were recruited to participate in an alcohol self‐administration paradigm as part of three studies. The purpose of the first study was to examine determinants of intravenous alcohol self‐administration in social drinkers. The second and third studies sought to examine the effects of medications on intravenous alcohol self‐administration in heavy drinkers .…”
Section: Methodsmentioning
confidence: 99%
“…While epidemiological studies have elucidated how broad patterns of drinking such as weekly and annual consumption levels affect health, few attempts have been made to characterize interindividual differences in alcohol consumption patterns during a single occasion. Recent work has shown that healthy young adults with a greater number of risk factors for alcohol use disorder have markedly higher rates of binging during a 2‐hour alcohol self‐administration session . However, it is not clear how drinking patterns differ between high‐risk social drinkers and those who have already developed heavy drinking patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge drinking is defined as drinking that results in blood alcohol concentration (BAC) levels at or above 0.08 g/dl (estimated as consuming at least 4 or 5 standard drinks in less than two hours for women and men, respectively). The mechanisms underlying binge drinking and related risky behaviors are unclear, but impulsivity or failure in inhibitory control during decision-making likely plays a role [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Binge drinking is defined as drinking that results in blood alcohol concentration (BAC) levels at or above 0.08 g/dl (estimated as consuming at least 4 or 5 standard drinks in less than two hours for women and men, respectively). The mechanisms underlying binge drinking and related risky behaviors are unclear, but impulsivity or failure in inhibitory control during decision-making likely plays a role [5-8].…”
Section: Introductionmentioning
confidence: 99%